Assessment of Vehicular Emission in Major Roadways within Ibadan Metropolis (2024)
The aggravation of road traffic as a result of rapid urbanisation and ineffective air quality management systems in urban centres pose a threat to public health. Air pollutants have significant adverse effect on the ecosystem. The study investigated the magnitude of air pollutants and relationship with vehicle emissions in three selected roads noted for their characteristic high traffic volume in Ibadan Metropolis. The concentration of carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxide (NOX) and sulphur dioxide (SO2) in the three selected locations (Beere market road, Mokola interchange, and Oyo road near the University of Ibadan Main Gate) were monitored using a Smart Sensor AS8900 model multi-gas detector and an IOT-based device setup known as the Raspberry pi 3+ B model with gas sensor add-on. The daily monitoring of emission was conducted for 24 days and results analysed using statistical methods. The average recorded pollutant emissions were below the standards set by the WHO. Pollutant emissions 21.81 ± 25.24ppm for carbon monoxide, 411.92 ± 145.11ppm for carbon dioxide, 0.04 ± 0.02ppm for nitrogen oxides and 0.004 ± 0.001ppm for sulphur dioxide. The concentration values of the pollutants varied with the traffic volume. Overall, the analysis indicated that there was no significant relationship between traffic volume and presence of pollutants in the study area. However, the regular agencies ought to further monitor traffic and other related pollutant emissions to ensure environmental safety